Sonochmical synthesis of zeolite a from collodal silica - Musthofa, M. (2008)
Zeolite A has been successfully prepared from colloidal silica at moderate temperature by sonochemical synthesis technique. In this study, the effect of ageing parameter (time and temperature) was investigated under ultrasound irradiation technique. XRD results showed that high crystallinity of zeolite A was obtained at 353 K for 60 minutes.